Industrial Effluent and Its Effect on Germination and Seedling Growth of Phaseolus aureus Roxb and Phaseolus mungo L. - Shetty, A. G. Malini (Research Highlights in Agricultural Sciences Vol. 6, 2022)
Industrial effluents are the second major source of water pollution and are making the water unfit for both agriculture and domestic use. But these effluents with proper dilution can be used as source of fertilizer in agriculture. In the present investigation, the treated effluent from BHEL was first analyzed for 13 physico-chemical parameters. Seed germination and seedling growth study of Phaseolus aureus and Phaseolus mungo was conducted in the second stage using different concentrations of [10, 25, 50, 75, 100 %] effluent. The percentage germination, shoot and root length, Vigour Index, Relative Toxicity were measured in all these treatments. The biochemical parameters like Protein, Proline, Carbohydrates and Phenol were assessed in plants in all these treatments. The morphological parameters showed increase in 10 and 25% concentration of effluent. The higher concentration had inhibitory effect on all morphological parameters. Vigour Index of the seedling showed decrease in higher concentration of treatment, while relative toxicity exhibited increase with increase in concentration of treatment. Among biochemical parameters protein revealed higher concentration in 10 and 25% treated plants. Other biochemical parameters showed higher values in 75 to 100% concentration. Bangalore being land locked city faces severe water scarcity, reuse of these effluents in agriculture is the best solution to mitigate this problem.